Harvesting temperature fluctuations as electrical energy using torsional and tensile polymer muscles. Issue 11 (28th September 2015) - Kim, Shi Hyeong; Lima, Márcio D.; Kozlov, Mikhail E.; Haines, Carter S.; Spinks, Geoffrey M.; Aziz, Shazed; Choi, Changsoon; Sim, Hyeon Jun; Wang, Xuemin; Lu, Hongbing; Qian, Dong; Madden, John D. W.; et al.
Abstract : Low-grade waste heat is harvested as electrical energy by employing thermally-powered torsional and tensile artificial muscles made from inexpensive polymer fibers used for fishing line and sewing thread. Abstract : Diverse means have been deployed for harvesting electrical energy from mechanical actuation produced by low-grade waste heat, but cycle rate, energy-per-cycle, device size and weight, or cost have limited applications. We report the electromagnetic harvesting of thermal energy as electrical energy using thermally powered torsional and tensile artificial muscles made from inexpensive polymer fibers used for fishing line and sewing thread. We show that a coiled 27 μm-diameter nylon muscle fiber can be driven by 16.7 °C air temperature fluctuations to spin a magnetic rotor to a peak torsional rotation speed of 70 000 rpm for over 300 000 heating–cooling cycles without performance degradation. By employing resonant fluctuations in air temperature of 19.6 °C, an average output electrical power of 124 W per kg of muscle was realized. Using tensile actuation of polyethylene-based coiled muscles and alternating flows of hot and cold water, up to 1.4 J of electrical energy was produced per cycle. The corresponding per cycle electric energy and peak power output, per muscle weight, were 77 J kg −1 and 28 W kg −1, respectively.